Economic and Humanistic Burden in Paediatric Patients with Atopic Dermatitis - Roselie Achten; Lisa van der Rijst; Marjanne Piena; Hedda Lamers; Fleur de Beer; Marjolein de Bruin-Weller; Marlies de Graaf (Medical Journals Sweden, 2023)
Data concerning the economic and humanistic burden in patients with paediatric atopic dermatitis (AD) and their families are scarce. This retrospective study investigated these burdens in paediatric patients with AD using maintenance treatment with topical corticosteroids and/or conventional systemic immunosuppressants. Patient-reported outcomes regarding quality of life, AD severity, and parental work-related impairment were completed at inclusion. Data on healthcare resource utilization and medication prescription were collected retrospectively over the previous 12 months. Patients were categorized into mild, moderate or severe AD, based on Eczema Area and Severity Index score and medication use. Costs per patient per year per AD severity category were calculated. A total of 101 patients (median age 11.0 years (interquartile range 7.5-14.0), 47.5% men) were included, of whom 38 had mild AD, 37 moderate AD, and 26 severe AD. Mean ± standard deviation (SD) total costs patient per year for mild, moderate and severe AD were €1,812 ± €1,280, €2,680 ± €3,127, and €5,861 ±  €3,993, respectively. Highest total direct and indirect costs were found in patients with severe AD, mainly due to higher healthcare and medication costs. Highest humanistic burden was found in patients with moderate AD. For example, the median (interquartile range) Patient-Oriented Eczema Measure score was significantly higher in these patients compared with mild and severe AD (19.0 (15.0-24.0) vs 12.0 (8.8-15.0) and 17.0 (9.5-22.0), respectively). AD in paediatric patients incurs considerable direct and indirect costs, especially in patients with severe AD. The high humanistic burden in patients with moderate AD underlines the need for effective and safe new treatment options for children with AD.